Circulating Cytokines and Coronavirus Disease: A Bi-Directional Mendelian Randomization Study - Li, Mengyu; Yeung, Chris Ho Ching; Schooling, C. Mary (Frontiers in Genetics, 2021)
Background: Immune system functioning is relevant to vulnerability to coronavirus disease (COVID-19). Cytokines are important to immunity. To further elucidate the role of the immune system in COVID-19, we used Mendelian randomization to assess comprehensively and bi-directionally the role of cytokines in COVID-19. Methods: We assessed primarily whether genetically different levels of 41 cytokines affected risk of any COVID-19 (laboratory confirmed, physician confirmed or self-reported, 36590 cases, 1668938 controls), and conversely if genetic risk of liability to any COVID-19 affected these cytokines (n ≤ 8293) using the most recent genome-wide association studies. We obtained inverse variance weighting estimates, conducted sensitivity analyses and used a Benjamini-Hochberg correction to account for multiple comparisons. We also assessed whether any findings were evident for hospitalized COVID-19 (hospitalized laboratory confirmed, 12888 cases, 1295966 controls). Results: Macrophage inflammatory protein-1β (more commonly known as Chemokine (C-C motif) ligands 4 (CCL4)) was inversely associated with COVID-19 (odds ratio (OR) 0.97 per SD, 95% confidence interval (CI) 0.96 to 0.99) but not after adjustment for multiple comparisons. This finding replicated for hospitalized COVID-19 (OR 0.93, 95% CI 0.89 to 0.98). Liability to any COVID-19 was nominally associated with several cytokines, such as granulocyte colony-stimulating factor and hepatocyte growth factor but not after correction. Conclusions: A crucial element of immune response to infection (CCL4) was related to COVID-19, whether it is a target of intervention to prevent COVID-19 warrants further investigation.